THE BRAVE SONS OF THE UZBEK PEOPLE (International Scientific Journal Alfraganus, 2025)
(Dedicated to the 80th anniversary of the Great Victory.) The contribution of the multinational people of Uzbekistan to the historic victory over fascism in World War II is immeasurable. Our people will never forget the courage and heroism of devoted fathers and grandfathers who defended today's peaceful, free, and prosperous life. The article highlights the bravery of the Uzbek people and their selfless service both at the front and on the home front during the war years.
Keywords: World War II; Uzbekistan; Great Victory; heroism; historical memory